A linear array for short range radio location and application systems - Kiani, Saad Hassan; Mahmood, Khalid; Altaf, Ahsan (Science and Information Organization, 2018)
Patch array antennas have primarily been good candidates for higher performance results in communication systems. This paper comprises of linear 1 × 4 patch antenna array study constructed on 1.575mm thick Roggers 5880 substrate with high gain of 12.8dB and focused directivity of 12.9dBi. The array network is fed using T Junction method showing well matched input impedance results. With higher performance parameters and reflection coefficient, voltage standing wave ratio, the proposed antenna array is suited for short range radiolocation and radio services application.
Keywords: Directivity; Gain; Linear Array; Radiolocation; Roggers 5880; Short Range Radio Applications; Voltage Standing Wave Ratio